Traditional Japanese Herbal Medicine Yokukansan Targets Distinct but Overlapping Mechanisms in Aged Mice and in the 5xFAD Mouse Model of Alzheimer’s Disease - Kaushik, Rahul; Morkovin, Evgeny; Schneeberg, Jenny; Confettura, Alessandro D.; Kreutz, Michael R.; Senkov, Oleg; Dityatev, Alexander (Frontiers in Aging Neuroscience, 2018)
Yokukansan (YKS) is a traditional Japanese herbal medicine that has been used in humans for the treatment of several neurological conditions, such as age-related anxiety and behavioral and psychological symptoms related to multiple forms of dementia, including Alzheimer’s disease (AD). However, the cellular and molecular mechanisms targeted by YKS in the brain are not completely understood. Here, we compared the efficacy of YKS in ameliorating the age- and early-onset familial AD-related behavioral and cellular defects in two groups of animals: 18- to 22-month-old C57BL6/J wild-type mice and 6- to 9-month-old 5xFAD mice, as a transgenic mouse model of this form of AD. Animals were fed food pellets that contained Yokukansan (1% w/w of dry components) or vehicle. After 8 weeks of YKS treatment, we evaluated the cognitive improvements in both the aged and 5xFAD transgenic mice, and their brain tissues were further investigated to assess the molecular and cellular changes that occurred following YKS intake. Our results show that both the aged and 5xFAD mice exhibited impaired behavioral performance in novel object recognition and contextual fear conditioning tasks, which was significantly improved by YKS. Further analyses of the brain tissue from these animals indicated that in aged mice, this improvement was associated with a reduction in astrogliosis, microglia activation and downregulation of the extracellular matrix, whereas in 5xFAD mice, none of these mechanisms were evident. These results show the differential action of YKS in healthy aged and 5xFAD mice. However, both aged and 5xFAD YKS-treated mice showed increased neuroprotective signaling through protein kinase B/AKT as the common mode of action. Our data suggest that YKS may impart its beneficial effects through AKT signaling in both 5xFAD mice and aged mice, with multiple additional mechanisms potentially contributing to its beneficial effects in aged animals.